2021
DOI: 10.1149/2162-8777/ac3acf
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition and Catalytic Performance of Hydrophobic PbO2 Electrode Modified by Surfactant OP-10

Abstract: A hydrophobic PbO2 electrode modified by surfactant OP-10 was prepared by electrodeposition. The electrode has good hydrophobic surface (the hydrophobic angle can reach 123°), high over point oxygen evolution (OEP) (1.60 V vs. SCE), and good service life (81 h). The electrode morphology and electrodeposition mechanism study found that the addition of OP-10 can help to build a dense PbO2 electrode surface, reduce the occurrence of side reactions, and promote the positive deposition of PbO2. As much as 30 mg L-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Influence of AA Concentration. Figure S3a displays the efficiency of AA by the OP-10&rGO-PbO 2 electrode at various preliminary AA configurations (10,20,30,40, 50 mg L −1 ) and its degradation kinetic curves within 120 min. In Figure S3a, the kinetic constant (k) and degradation efficiency gradually declined as the pollutant concentration increased.…”
Section: Electrocatalytic Oxidation Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Influence of AA Concentration. Figure S3a displays the efficiency of AA by the OP-10&rGO-PbO 2 electrode at various preliminary AA configurations (10,20,30,40, 50 mg L −1 ) and its degradation kinetic curves within 120 min. In Figure S3a, the kinetic constant (k) and degradation efficiency gradually declined as the pollutant concentration increased.…”
Section: Electrocatalytic Oxidation Performancementioning
confidence: 99%
“…However, rGO loading often falls off from the PbO 2 electrode surface, shortening the service life of PbO 2 electrodes. , Fortunately, previous work confirmed that OP-10, as a surfactant, can improve the surface topography of PbO 2 and make the electrode more compact. OP-10 can facilitate the positive deposition of the PbO 2 electrode, making the PbO 2 grain finer and better hydrophobic . Also, it was found that OP-10 can better dissolve rGO into PbO 2 plating solution and prevent rGO agglomeration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorine-containing surfactants due to hydrophobization increase the bond strength [18], which leads to an increase in the overvoltage of oxygen. Such data are confirmed by XPS data, where one can see an increase in the proportion of inert oxygen-containing radicals, which was also observed in the case of the use of fluorine as an additive to the electrolyte of PbO2 deposition [10].…”
Section: Fig 3 Adsorption Isotherm Of C8f17so3k On Pbo2 Powder In The...mentioning
confidence: 99%
“…There is a niche for research here, because such electrodes are able to influence the binding energy of oxygen-containing particles by hydrophobizing the surface. According to the literature [18], this effect will create conditions for greater reactivity in the oxidation reactions of organic compounds. In this case, we were interested in finding out the effect of the length of the perfluorinated hydrocarbon chain on the properties of the coating.…”
Section: Introductionmentioning
confidence: 99%